Social Class and Poverty in American Society in the 2000’s Era as Seen in Suzanne Collins’s The Hunger Games Novel - Heidy Putri Permatasari (Lexicon, 2015)
The Hunger Games by Suzanne Collins tells about the survival game in one country and the participant of the game is obtained by random election in each district of the country. The objective of this paper is to reveal the economic inequality in American society in the 2000’s era that is depicted in the novel. The method used is based on library research. The main data of the study were The Hunger Game novel. The secondary data to support the analysis were books, articles, and encyclopedias. Additional information is also taken from the internet.The theory applied in this article is mimetic approach. It analyses the character, setting, plot, and theme. The findings show that there is a gap between the upper class and the lower class. The lower class has to struggle to still alive, while the upper class becomes richer. The upper class also has more power than the lower class. Then, the lower class is suffering from the poverty. Social class is one of thing that determines people to have more opportunity in the society.It can be concluded that the novel is about the reflection of the society condition of American society in the 2000’s era. The author of the novel describes the social gap, social class, and poverty in American society very clearly and in detail. Therefore,there any differences between The Hunger Games and social background.